2008
DOI: 10.1002/elps.200700552
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, modification, and application of poly(methyl methacrylate) microfluidic chips

Abstract: Poly(methyl methacrylate) (PMMA) is particularly useful for microfluidic chips with the features of low price, excellent optic transparency, attractive mechanical and chemical properties, ease of fabrication and modification, biocompatibility, etc. During the past decade, significant progress in the PMMA microfluidic chips has occurred. This review, which contains 120 references, summarizes the recent advances and the key strategies in the fabrication, modification, and application of PMMA microfluidic chips. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(93 citation statements)
references
References 123 publications
0
87
0
3
Order By: Relevance
“…Polymeric materials can be divided into two main groups: elastomers (including for example, PDMS [20] and polyurethane [21]) and thermoplastics (comprising polycarbonate and PMMA). Due to its high mechanic and chemical stability, optical transparency, and excellent dielectric properties [22], PMMA has become one of the most popular substrates for ME systems. These properties have also allowed for the development of different fabrication methods including hot embossing [23], injection molding [24], and laser engraving [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric materials can be divided into two main groups: elastomers (including for example, PDMS [20] and polyurethane [21]) and thermoplastics (comprising polycarbonate and PMMA). Due to its high mechanic and chemical stability, optical transparency, and excellent dielectric properties [22], PMMA has become one of the most popular substrates for ME systems. These properties have also allowed for the development of different fabrication methods including hot embossing [23], injection molding [24], and laser engraving [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The PMMA microspheres used in this study exhibited ideal characteristics in terms of inertness, stability at room temperature, availability, low production cost, physical consistency at the implantation site similar to that of un implanted tissue, and durability [7][8][9][10][11][12]18,19,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that polymethylmethacrylate (PMMA) is biocompatible, does not generate an inflammatory response when implanted under the skin, and remains at the implantation site for long periods [11,18,19]. Because of its small number of side effects and its lasting results, PMMA is believed to be a good solution for dermal filling.…”
Section: Introductionmentioning
confidence: 99%
“…PMMA, used for fabricating the main modules of the system, has low hydrophobicity and can be easily modified. 29 Most importantly, it is sufficiently UV permeable to allow the hapten immobilization. Elasticity of PDMS 30 has been instrumental in achieving the functionality of the ribbons used in the micropump and valves as well as leakage-proof sealing to flat surfaces using the BJIB module-to-module interconnections.…”
Section: Fabrication Of µFia Based Amperometric Immunosensormentioning
confidence: 99%